Motivasi Belajar Sebagai Perantara Menjembatani Variasi Gaya Mengajar Terhadap Hasil Belajar - Susana Indriati; Edi Fitriana Afriza; Bakti Widyaningrum (JURNAL PENA EDUKASI, 2024)
Abstract:Â  A person's success in pursuing a learning process at a particular educational level can be assessed based on the learning outcomes. The focus of this research is on low student learning outcomes. This research aims to determine the impact of differences in teacher teaching styles on student learning outcomes through student learning motivation. This research adopts a quantitative survey research method. The sample for this research was a proportional random sample of 198 students. The data analysis technique used is path analysis. From the results of the path analysis, the regression equations Z = 37.884 + 0.558ð‘‹ + 0.8300e1 and Y = 60.859 + 0.455ð‘‹ + 0.191Z + 0.8124ð‘’2 are obtained. Based on the research results, it is known that there is a positive and significant influence between variations in teacher teaching styles on student learning motivation, variations in teacher teaching styles on student learning outcomes, and student learning motivation on student learning outcomes. Furthermore, student learning motivation is thought to mediate the influence of variations in teacher teaching styles on student learning outcomes.Keywords: teaching; styles;variationAbstrak: Keberhasilan seseorang menekuni suatu proses belajar pada suatu jenjang pendidi-kan tertentu dapat dinilai dari hasil belajar itu sendiri. Fokus penelitian ini adalah pada ren-dahnya hasil belajar siswa. Tujuan penelitian ini adalah untuk mengetahui dampak perbedaan gaya mengajar guru terhadap hasil belajar siswa melalui motivasi belajar siswa. Penelitian ini mengadopsi metode penelitian survei kuantitatif. Sampel penelitian ini adalah sampel acak proporsional yang berjumlah 198 siswa. Teknik analisis data yang digunakan adalah analisis jalur. Dari hasil analisis jalur diperoleh persamaan regresi Z = 37,884 + 0,558ð‘‹ + 0,8300e1 dan Y = 60,859 + 0,455ð‘‹ + 0,191Z + 0,8124ð‘’2. Berdasarkan hasil penelitian diketahui bahwa ter-dapat pengaruh positif dan signifikan antara variasi gaya mengajar guru terhadap motivasi belajar siswa, variasi gaya mengajar guru terhadap hasil belajar siswa, dan motivasi belajar siswa terhadap hasil belajar siswa. Lebih lanjut, motivasi belajar siswa diduga memediasi pengaruhÂ  variasi gaya mengajar guru terhadap hasil belajar siswa.Kata kunci: gaya; mengajar; variasi